Peran Headline dalam Interaksi Audiens pada Konten Instagram @cnbcindonesia - Najla Aulia Anchar; Wahyu Budi Priatna (Journal of Creative Student Research, 2026)
The growth of social media has transformed news distribution, with Instagram emerging as a key platform for reaching wider audiences. In a dense digital content ecosystem, headlines act as the first element shaping audience attention and interaction. This study aims to analyze the role of headlines in influencing audience interaction on @cnbcindonesia’s Instagram content and their impact on engagement indicators such as likes and comments. This research employs a descriptive qualitative method, with data collected through in-depth interviews and observation. Informants include two social media reporters from CNBC Indonesia and two active followers selected through purposive sampling. Data analysis follows the Miles, Huberman, and Saldaña model and is interpreted using the AISAS framework. The findings show that headlines play a significant role in audience responses; emotional and relevant headlines are more effective in attracting attention and interest and can trigger comments before the full content is read. This indicates that the AISAS model in social media does not always operate linearly, while sharing decisions are influenced more by the overall informational value of the content.